Status of maternal serum B vitamins and pregnancy outcomes: New insights from in vitro fertilization and embryo transfer (IVF-ET) treatment - Zhang, Ling; Wu, Li-mei; Xu, Wei-hai; Tian, Yu-qing; Liu, Xu-ling; Xia, Chen-yun; Zhang, Lin; Li, Shi-shi; Jin, Zhen; Wu, Xiang-li; Shu, Jing (Frontiers in Nutrition, 2022)
The influence of B vitamins on human fertility and infertility treatments remains elusive. Therefore, this study investigated the association of most B vitamins with IVF-ET outcomes. A total of 216 subjects aged <35 year in their first oocyte retrieval cycle were recruited. Blood samples from the participants were collected before the oocyte pick-up procedure, and serum levels of riboflavin, niacin, pantothenic acid, vitamin B6 (including PA and PLP), folate, and methylmalonic acid (MMA) were detected using high-performance liquid chromatography–tandem mass spectrometry (HPLC-MS/MS). Endpoints were classified into three groups according to tertiles (lower, middle, and upper) of each vitamin index, and the association of the serum vitamin status with intermediate and clinical outcomes was analyzed using a generalized estimating equation model. Higher riboflavin levels were associated with elevated probabilities of high-quality embryos, as well as clinical pregnancy after embryo transfer. A greater likelihood of transferable embryos was found in the middle tertile of serum folate. Similarly, a negative correlation of serum MMA, a marker of vitamin B12 deficiency, with high-quality embryos was identified. No significance was observed for other vitamins in terms of all endpoints. Therefore, sufficient levels of pre-conception riboflavin, folate, and vitamin B12 are recommended for successful infertility treatment and pregnancy planning; further evidence is needed to confirm our conclusion.